Antenna Element Index Modulation for Frequency Diverse Array - Gaojian Huang; Yuan Ding; Vincent Fusco; Shan Ouyang (International Journal of Antennas and Propagation)
In this paper, we propose a new architecture and provide performance analysis for frequency diverse array (FDA) Radar combined with the index modulation (IM) techniques. Here, the IM concept is applied upon frequency offsets in an FDA. Information is transmitted by a dynamically selected subset of antenna element indices applying predefined carrier frequency offsets, which generate different radiation patterns. It is shown that this enables the capability for simultaneous wireless communication and FDA Radar that has the range-angle coupling issue resolved.